Enhancing Information Retention of Forensic Science Students: Incorporating a Simulated Crime Scene Practicum in the College Classroom (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The purpose of this research was to investigate whether crime scene simulations benefit the learning process in terms of retention of knowledge.  By providing a real-word experience via the Applied Learning pedagogy, the comprehension of the basic foundations of forensic science were indeed retained and reinforced through the incorporation of a mock crime scene in the classroom.  A total of 50 undergraduate students majoring in criminal justice participated and were evaluated using three different assessment measures employed throughout the practicum: feedback, reflection, and debriefings.  This qualitative research uncovered that students’ retention of the theories and concepts continued past the midterm examination while the instructor benefited from a multi-assessment approach to gauging student performance.  Additionally, this research also found that learners benefited in ways beyond the scope of this study; they also came away with practical realizations relating to the benefits of collaboration and an understanding of how this course prepares them for careers in law enforcement.